Renewable Energy and Sustainable Economic Development in Nigeria: A Case Study of Rivers State (2000 to 2022) - Udoinyang, Nathan; Sunday, Favour Chizoba; Daniel, Reuben (Journal of Environmental and Energy Economics, 2024)
Using the years 2000 to 2022, this research looks at renewable energy and sustainable economic growth in the Nigerian state of Rivers. This study utilized a survey methodology to collect data from the whole population of Rivers state. A total of 318 people from each of the three senatorial districts filled out the survey, and the researchers used the Taro Yamane formula to determine that a sample size of 400 was appropriate. With a mean criteria of 3.0, the statistical tools of the Statistical Package for the Social Sciences (SPSS) were used to analyze the study's research topics. Reviewing the effects of renewable energy on long-term economic growth in Rivers State, we find that it helps with energy efficiency, keeps socioeconomic development going, lowers emissions of greenhouse gases, air pollution, and climate change, and raises living standards. Lack of renewable energy policy implementation, insufficient investor attraction mechanisms, insufficient technology, insufficient renewable energy developers, insufficient credit facilities accessible to renewable energy developers, and low renewable energy awareness are all mentioned as obstacles to the state of Rivers, Nigeria's renewable energy sector in the study. Sustainable economic development can be achieved through the use of renewable energy, according to the study. The researchers urged the government and policymakers in Rivers State, Nigeria, to train more renewable energy developers, establish credit facilities and an enabling environment for the exploitation of renewable energy, allocate funds, and make renewable energy policy.